Positive streamers in air of varying density: experiments on the scaling of the excitation density. (19th January 2015) - Dubrovin, D; Nijdam, S; Clevis, T T J; Heijmans, L C J; Ebert, U; Yair, Y; Price, C
Abstract: Streamers are rapidly extending ionized finger-like structures that dominate the initial breakdown of large gas volumes in the presence of a sufficiently strong electric field. Their macroscopic parameters are described by simple scaling relations, where the densities of electrons and of excited molecules in the active streamer front scale as the square of the density of the neutral gas. In this work we estimate the absolute density of nitrogen molecules, excited to the C 3 Π u state that emit photons in the 2P–N2 band, by radiometrically calibrated short exposure intensified imaging. We test several pressures (100, 200 and 400 mbar) in artificial air at room temperature. Our results provide a first confirmation for the scaling of the density of excited species with the gas density. The method proposed here is particularly suitable to characterize the excitation densities in sprite streamers in the atmosphere.